Impact of Industry 4.0 on Human Resource Process - Vidhya Priya, Periasamy; Sundharesalingam, Poosappan (Ushus Journal of Business Management, 2022)
This paper is aimed at understanding the impact of industry 4.0 on the Human Resources Management Process by use of specific technologies. Industry 4.0 made HR Processes easy, accurate, and fast. The study focuses mainly on, the efficiency of AI and HR automation based on time consumption and error-free process and how far it is efficient in engaging employees with Data Analytics. In this research, the impact of Industry 4.0 on HR is assessed by getting responses from HR Managers and HR Staff in the organisation. Descriptive research design is used in this project and the Judgmental sampling method is used for samples. Here the impact of these technologies is assessed with respective employee engagement, process automation, and cost-effectiveness.